3-(4-Fluorofenilselenil)-2,5 difenilselenofeno produz ação do tipo-antidepressiva em diferentes modelos de depressão em camundongos - Gai, Bibiana Mozzaquatro (2014)
Selenophenes are a promising class of heterocyclic selenium-containing compounds presenting important pharmacological properties. Based on selenium well-described role on mood regulation and since depression is a serious and prevalent disease affecting a wide part of the world s population, the main aim of this work was to investigate de antidepressant-like action of 3-(organosseleno)-2,5-diphenyl-selenophenes in mice. The pharmacological effect of these compounds was analyzed by using different experimental models of depression and results were shown by three scientific articles. Firstly, results of Article 1 demonstrated the antidepressant-like action of five selenophene compounds. H-DPS, CH3-DPS, Cl-DPS, FDPS and CF3-DPS reduced the total immobility time of mice evaluated in the forced swimming test (FST), which seems to be related to their chemical structure. The antidepressant-like action of F-DPS was observed at lower doses than other selenophenes e involves the phosphorylation of extracellular-signal-regulated kinases (ERK), whose signaling pathway is commonly modulated by antidepressant drugs. Articles 2 and 3 investigated the pharmacological effect of F-DPS in mouse models of depression induced by both neuropathic pain and chronic corticosterone administration, respectively. Both the acute and subchronic treatments with F-DPS significantly reversed the depression-related behavior produced by partial sciatic nerve ligation (PSNL), whereas pain sensibility was only reduced after repeated treatment with this selenophene. Besides, repeated administration of the glucocorticoid hormone corticosterone induced behavior, endocrinal and neurochemical changes similar to those clinically observed in depression, which were also reversed by treatment of animals with F-DPS. Based on these data, the mechanisms of pharmacological action of this organoselenium compound seem to involve, at least in part, a modulation of glutamatergic and serotonergic systems, the hypothalamic-pituitary-adrenal (HPA) axis regulation and changes on neuronal pathways related to the synaptic plasticity. Together, the results shown in this thesis suggest the pharmacological properties of selenophene compounds, particularly F-DPS, as an interesting tool in the study and development of future therapies for depressive disorders.